ANALISIS PENGARUH ANGKATAN KERJA DAN INFLASI TERHADAP PERDAGANGAN INTERNASIONAL DI INDONESIA DALAM KAJIAN EKONOMI MAKRO ISLAM - Amsah Hendri Doni; Iiz Izmuddin (EKONOMIKA SYARIAH : Journal of Economic Studies, 2018)
This article focused on analyse (1) influence of labor force and consumer price index to international trade in Indonesia. Data used time series data of (2002 - 2016). This article use analyzer model multiple linear regression method. The result of research conclude that (1) labor force have an effect on by signifikan to international trade in Indonesia. The increase of to labor force, will be the increase of international trade in Indonesia. (2) inflation (consumer price index) have an effect on by signifikan to international trade in Indonesia. The increase of to inflation (consumer price index), will be the increase of international trade in Indonesia. (3) labor force and inflation (consumer price index) simultan have an effect on by signifikan to international trade in Indonesia. The increase of to labor force and inflation (consumer price index) simultan will be the increase of international trade in Indonesia.